2022
DOI: 10.1177/09731342231163391
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Disordered Eating Among a Sample of Indian Adolescents: The Role of Online Activity, Social Anxiety and Social Support

Abstract: Background: Although the concept of a slim body was first introduced in Western societies, body dissatisfaction and disordered eating became a globalized issue, and appeared in India and other Asian cultures as well. However, we know much less about the background variables in this region. Aim: To further examine potential risk and protective factors for disordered eating, we aimed to detect the role of online activity (smartphone addiction, time spent online), social anxiety and social support as well as Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(59 reference statements)
0
0
0
Order By: Relevance
“…In fact, peer support could be a protective factor of the appearance of EDs symptoms for adolescents whose parents own a controlling parenting style. These individuals perceive the positive reinforcement they need in their equal relationships (Pace et al, 2018;Piko et al, 2023). On the contrary, low-quality relationships based on lack of support, feeling alienated or less self-validation have been identified as risk factors of EDs (Sharpe et al, 2014;Beckers et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, peer support could be a protective factor of the appearance of EDs symptoms for adolescents whose parents own a controlling parenting style. These individuals perceive the positive reinforcement they need in their equal relationships (Pace et al, 2018;Piko et al, 2023). On the contrary, low-quality relationships based on lack of support, feeling alienated or less self-validation have been identified as risk factors of EDs (Sharpe et al, 2014;Beckers et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding interpersonal relationships, seven studies identified the influence of these variables on eating behaviors. Perceived peer support was identified as a protective moderator in the relationship between paternal achievement oriented psychological control and EDs symptomatology (Pace et al, 2018;Piko et al, 2023). However, characteristics related with low-quality friendships such as conflicts among friends (Beckers et al, 2023), provide less self-validations, feelings of alienation and perception of less helpful friendships are associated with more probabilities of presenting symptoms of EDs (Sharpe et al, 2014).…”
Section: Family and Peers' Influencementioning
confidence: 95%
See 1 more Smart Citation